2012
DOI: 10.1073/pnas.1203468109
|View full text |Cite
|
Sign up to set email alerts
|

Cross-dressed CD8α + /CD103 + dendritic cells prime CD8 + T cells following vaccination

Abstract: Activation of naïve cluster of differentiation (CD)8 + cytotoxic T lymphocytes (CTLs) is a tightly regulated process, and specific dendritic cell (DC) subsets are typically required to activate naive CTLs. Potential pathways for antigen presentation leading to CD8 + T-cell priming include direct presentation, cross-presentation, and cross-dressing. To distinguish between these pathways, we designed single-chain trimer (SCT) peptide-MHC class I complexes that can be recognized as intact molecules but cannot del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…This is in striking contrast to antigens delivered by recombinant viruses or bacteria, which can elicit huge responses . An adjuvant that promotes an efficient CD8 + T‐cell response will almost certainly need to act via cross‐presenting or cross‐dressing DCs and, in this respect, CD103 + dDCs are prime candidates . It is therefore important to understand the effects of adjuvants on CD103 + dDCs and, to the best of our knowledge, the study presented herein is the first to do so.…”
Section: Discussionmentioning
confidence: 98%
“…This is in striking contrast to antigens delivered by recombinant viruses or bacteria, which can elicit huge responses . An adjuvant that promotes an efficient CD8 + T‐cell response will almost certainly need to act via cross‐presenting or cross‐dressing DCs and, in this respect, CD103 + dDCs are prime candidates . It is therefore important to understand the effects of adjuvants on CD103 + dDCs and, to the best of our knowledge, the study presented herein is the first to do so.…”
Section: Discussionmentioning
confidence: 98%
“…Exchange of membrane molecules/ Ags between immune cells has been observed for a long time (4,5), but the mechanisms and functional consequences of these transfers have not been completely elucidated. Nevertheless, several studies (3,(6)(7)(8)(9) reported that transfer of peptide-MHC complexes on DCs is a potential additional mechanism for activating T cells and referred to the process as "DC cross-dressing," a term originally coined by Yewdell and Haeryfar (10). Although cross-dressing has been clearly shown in conventional myeloid DCs (mDCs), this phenomenon has never been reported in plasmacytoid DCs (pDCs).…”
Section: O Ptimal Activation Of Tumor-specific Cytotoxic Cd8 + T Celmentioning
confidence: 99%
“…This fusion protein, whose N-terminal part lacks a defined tertiary structure, does feed well into the MHC class I antigen processing machinery of the cell expressing it endogenously, but does not give rise to substantial levels of stable protein, that is, no detectable GFP expression, and thus likely represents a very poor substrate for crosspresentation (Probst et al, 2003). The absence of priming by DCs that do not carry the DIETER transgene itself (Muth et al, 2014) also rules out functionally relevant DC-to-DC antigen transfer by means other than cross-presentation, such as the transfer of fully assembled peptide/MHC complexes by trogocytosis that has been dubbed "cross dressing" (Dolan et al, 2006;Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%